Réponses

Meilleure réponse !
2014-03-22T15:29:46+01:00
G(4)=-14          si g(x)=ax+b on a  4a+b=-14 soit b=-14-4a, on remplace l'expression de b
g(-10)=35         dans l'autre équation:                  -10a+b=35 soit -10a-14-4a =35
                                                                             -14a=35+14
                                                                               14a=-49
                                                                                   a=-49/14 or 49=7x7 et 14=7x2
                                                                                   a=-7/2
                                                         b = 14-4a
                                                         b =14-4x7/2
                                                         b=14-2x2x7/2
                                                         b=14-2x7
                                                         b=14-14
                                                         b=0
on a bien une fonction linéaire g(x)=-7x/2